Collaborative Practices Advancing Socio-Emotional Development in Inclusive Early Education - Anik Nurul; Hidayah (Al-Qalam Institute, 2026)
Socio-emotional development in inclusive early education requires coordinated support across relational systems. This study aims to examine how collaborative practices advance children’s emotional regulation, peer relationships, and classroom belonging. A qualitative multiple case study design was employed involving 15 informants consisting of classroom teachers, special education teachers, principals, and parents from inclusive early childhood education centers with established collaboration structures. Data were collected through in-depth interviews, non-participant observations, and document analysis, and analyzed using interactive qualitative procedures. The findings reveal that structured collaboration reduced emotional disruptions, interdisciplinary teamwork increased peer reciprocity, and documented family participation strengthened children’s sense of belonging. The novelty of this research lies in integrating socio-emotional learning with collaborative inclusion frameworks into a systemic model. The study recommends institutionalizing structured coordination, co-teaching practices, and participatory family engagement to sustain inclusive socio-emotional development.